Transcending the Scottish Postmodern City: Ken MacLeod’s Future Urban Geographies - Aliaga-Lavrijsen, Jessica (Complutense Journal of English Studies, 2021)
A place cannot exist if it has not been imagined, if it has not been perceived, as Alasdair Gray famously stated. Scottish Science Fiction goes a step further by emphasizing the need not only to recognise and represent Scottish places, but also to recreate and to re-imagine them in its possible futures. To (re-)imagine Scotland and its places means also to envision its potential spaces. Ken MacLeod is one of the figures who has successfully managed to set Scotland on the Science Fiction map. His novels Intrusion (2012) and Descent (2014) are remarkable examples of what some critics have called ‘Transmodern fiction’. Both are set in urban Scotland in the near-future and they portray new configurations of place. My analysis will focus on the interconnectedness of place as presented in both novels, creating a new territory that transcends the Scottish Postmodern urban geographies. In MacLeod’s fiction, a Transmodern urban place is conceived, where the glocal and the virtual meet in a new multifold reality without ever losing its local specificity